2010
DOI: 10.4161/cc.9.16.12553
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in cancer associated fibroblasts drives tumor-stroma co-evolution

Abstract: Loss of stromal fibroblast caveolin-1 (Cav-1) is a powerful single independent predictor of poor prognosis in human breast cancer patients, and is associated with early tumor recurrence, lymph node metastasis and tamoxifen-resistance. We developed a novel co-culture system to understand the mechanism(s) by which a loss of stromal fibroblast Cav-1 induces a "lethal tumor microenvironment." Here, we propose a new paradigm to explain the powerful prognostic value of stromal Cav-1. In this model, cancer cells indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
226
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 378 publications
(269 citation statements)
references
References 84 publications
11
226
2
5
Order By: Relevance
“…For example, cancer cells induce oxidative stress in neighboring cancerassociated fibroblasts (CAFs), which results in production of nutrients such as lactate from the CAFs that then promote survival of cancer cells; these effects are most concentrated in tumor adjacent CAFs but may be able to diffuse to more distant stromal cells. 10 Here, we demonstrate that gene expression profiles of adipose tissue differ based on distance from the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cancer cells induce oxidative stress in neighboring cancerassociated fibroblasts (CAFs), which results in production of nutrients such as lactate from the CAFs that then promote survival of cancer cells; these effects are most concentrated in tumor adjacent CAFs but may be able to diffuse to more distant stromal cells. 10 Here, we demonstrate that gene expression profiles of adipose tissue differ based on distance from the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells first secreted hydrogen peroxide (H 2 O 2 ) to induce oxidative stress in adjacent fibroblasts as a form of accelerated aging; [30][31][32] at the same time, the cancer cells mounted an antioxidant defense by upregulating antioxidant proteins, such as TIGAR and peroxiredoxins. 29,33,34 Oxidative stress in the cancer-associated fibroblasts increased stromal ROS production, activating two major transcription factors, namely, HIF1a and NFκB, which both function as master regulators of autophagy, mitophagy, aerobic glycolysis as well as inflammation. 30,[33][34][35][36] As a consequence, the stromal fibroblasts would produce high-energy nutrients (L-lactate, ketones and glutamine).…”
Section: Visualizing Two-compartment Tumor Metabolism: Hyperactivatiomentioning
confidence: 99%
“…49,50 We measured the change of total area covered by HuH7 using phase contrast images of the co-culture chip, which was processed by ImageJ software (detailed procedure illustrated in Figure S3, supplementary material). 52 It was observed that the coverage of tumor cells increased significantly after day 4 ( Figure 6(a)).…”
Section: Resultsmentioning
confidence: 99%